2023
DOI: 10.1111/pde.15223
|View full text |Cite
|
Sign up to set email alerts
|

Acne incidence in preadolescents and association with increased body mass index: A population‐based retrospective cohort study of 643 cases with age‐ and sex‐matched community controls

Abstract: Background/Objectives Little is known about acne incidence in preadolescents and its potential association with body mass index (BMI). Our study aims to determine acne incidence in preadolescents and its association with BMI. Methods A population‐based retrospective cohort study identified 7‐ to ≤12 year‐olds with an initial acne diagnosis during 2010–2018, and incidence was calculated. Two age‐ and sex‐matched controls without acne were randomly selected per case, and BMI was recorded. Results A total of 643 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Rodriguez Baisi et al found that preadolescents with acne were more likely to be obese compared to those without acne [ 26 ]. Tsai et al study supported the positive associations between BMI and acne development, and showed the severity of acne may start to worsen in the upper grades of elementary school [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez Baisi et al found that preadolescents with acne were more likely to be obese compared to those without acne [ 26 ]. Tsai et al study supported the positive associations between BMI and acne development, and showed the severity of acne may start to worsen in the upper grades of elementary school [ 27 ].…”
Section: Discussionmentioning
confidence: 99%